Pemeriksaan Kesehatan dan Senam Lansia Dalam Peningkatan Kualitas Hidup Lansia di Desa Karta Dewa - aal, Alkhusari; Dani Prasetyo; Novalia Efrianty; amien saputra (Ukhuwah : Jurnal Pengabdian Kepada Masyarakat, 2025)
Health program in the aspect of health services for the elderly which is implemented through the Posyandu program by involving the participation of the elderly, families, community leaders and social organizations in its implementation. The purpose of this activity is to improve the quality of life of the elderly through regular health checks and structured elderly exercise programs. The method of this community service activity includes basic health checks (blood pressure, and simple physical examinations) and the implementation of the elderly exercise program which was carried out on February 12, 2025. Data collection by implementing the elderly posyandu with the method of health checks and elderly exercise. The results of this community service are the elderly actively and enthusiastically in community service activities attended by 25 elderly, students and posyandu officers at the Karta Dewa Village Hall, Pali Regency. The benefits of this activity help identify elderly health problems early and improve health status. The problems experienced by the elderly experience almost 70% of recurrent hypertension due to lack of control to health services, forgetting to take medication, lack of family role, lack of daily exercise so that the quality of life of the elderly is reduced. This activity is expected that Karta Dewa Village can carry out this activity sustainably to improve the quality of life of the elderly.